Clinical significance of ROS1 5' deletions in non-small cell lung cancer. (September 2019) - Capizzi, Elisa; Dall'Olio, Filippo Gustavo; Gruppioni, Elisa; Sperandi, Francesca; Altimari, Annalisa; Giunchi, Francesca; Fiorentino, Michelangelo; Ardizzoni, Andrea
Highlights: NSCLC patients with ROS1 fusions are eligible for first-line therapy with Crizotinib. Diagnostic FISH criteria were mirrored from ALK, including tumors with 5' deletions. Response to Crizotinib in patients with ROS1 deletions has never been investigated. We show that 5' ROS1 deletions are linked with a chance of response to Crizotinib. Confirmation of ROS1 fusions NGS is beneficial to define the ROS1 fusion partners. Abstract: Objectives: Patients harboring rearrangements of the ROS1 gene are eligible for first-line therapy with Crizotinib, which represents the best available treatment option. Diagnostic criteria, based on break-apart fluorescence in situ hybridization, were mirrored from ALK by analogy and include tumors with 5' deletions. However, the probability of response to Crizotinib in patients with 5' deletion in ROS1 is unknown given the rarity of this condition. Materials and methods: We hereby describe clinical outcome of 8 NSCLC patients harboring a 5' deletion at FISH treated with Crizotinib Results: Three out of 4 cases whose 5' deletion was confirmed by NGS as a ROS1/EZR fusion displayed an objective response to Crizotinib while a case with ROS1/SDC4 fusion did not. By contrast, among the 4 cases where NGS did not detect ROS1 gene fusions only 2 patients responded to crizotinib therapy with one also harboring a concomitant EML4-ALK rearrangement. Conclusion: 5' ROS1 deletions detected by FISH are associated with a high chance of response to Crizotinib in NSCLC, similarly to canonical ROS1 split-apart FISH rearrangements. However, the confirmation of the ROS1 gene fusion with at least another method, such as NGS, seems beneficial in order to define the ROS1 fusion partner and to avoid possible false positive results.